Optimization Of Power From Food Waste Using Membrane-less Microbial Fuel Cell - Anandita, Nadira (Pusat Pengajian Teknologi Industri, 2020)
Fossil fuels have supported the industrialization and economic growth of countries during the past centuries and it is clear that they cannot indefinitely sustain in a longer time. In this study, Microbial Fuel cell (MFC) had potential solution to generate electricity power and at the same time could reduce the abundant of food waste (1.64 kg/daily, around 8 tonnes/year) which dumped in the landfill. The MFC operated electrochemically incorporate electrogenic bacteria (EB) acted as a biocatalyst in order to produce electricity. The performance of the MFC using food waste is evaluated using one-factor-at-a-time (OFAT) method. the optimization performance of the MFC using food waste was evaluated using method of one factor at one time (OFAT) and it was focused to pH for power generation. To determine the generated electricity the polarization curve was used to evaluate the performance of MFC. The chemical oxygen demand (COD) of food waste is studied. Optimization of pH condition in MFC under certain pH ranging from 5 to 9, with other condition. Results shows that pH 8 is the most suitable pH for Bacillus strain that was chosen for this experiment. With voltage generated resulted 807 mV, highest biomass produced 35.46 mg/L, and power density produced 373.3 mW/m2. In conclusion, pH environment condition in MFC will affect the efficiency of performance for energy production. The increase in EB biomass also increased the voltage in the ML-MFC, proving that EB biomass and voltage were associated with growth.